2007
DOI: 10.1002/ceat.200700247
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of the Fluidized Bed Drying of Cubic Materials

Abstract: The unsteady-state simultaneous heat and mass transfer between gas and potato cubes during the drying process in a batch fluidized bed was described by a mathematical model. Mass transfer was considered to occur in three dimensions whereas heat transfer between the gas and dried material was assumed to be lumped. It was found that the model could describe the drying process with acceptable accuracy. The moisture profile inside the material at any cross-section and at any time can be predicted by the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Air‐drying of most agro‐food products displays no constant rate period and the diffusion inside the particles is well represented by single‐phase molecular diffusion (Hatamipour and Jazini 2007). In most studies carried out on drying, diffusion is generally accepted to be the main mechanism during the transport of moisture to the surface to be evaporated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air‐drying of most agro‐food products displays no constant rate period and the diffusion inside the particles is well represented by single‐phase molecular diffusion (Hatamipour and Jazini 2007). In most studies carried out on drying, diffusion is generally accepted to be the main mechanism during the transport of moisture to the surface to be evaporated.…”
Section: Resultsmentioning
confidence: 99%
“…2004), kiwi fruit (Simal et al. 2005), okra (Doymaz 2005), chard leave (Alibas 2006), potato cubes (Hatamipour and Jazini 2007), fever leaves (Sobukola and Dairo 2007) and pomegranate arils (Kingsly and Singh 2007).…”
Section: Resultsmentioning
confidence: 99%
“…3 displays the moisture content profiles of sawdust dried at 70°C, 80°C, and 90°C, respectively. It can be observed that moisture contents change in a decreasing exponential trend which is quite typical for most biomaterials including wood-based materials [19][20][21][22][23][24][25].…”
Section: Reaction Engineering Approachmentioning
confidence: 91%
“…The results obtained on the basis of reliable mathematical model and numerical analysis enable prediction of the relevant process parameters required for design of a particular device and optimization of the process itself. A good model and its numerical solution can successfully substitute lengthy and expensive experiments (Hatamipour and Jazini, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Song and Nam (2005; numerically studied the freeze-drying characteristics of food products with planar, slab-shaped and cylindrical geometries including the conjugate heat and mass transfer, sublimation of ice, and motion of sublimation interface. Hatamipour and Jazini (2007) simulated fluidized-bed drying of a cubic potato sample with a straightforward mathematical model. More recently, Perre, et al (Perre, 2010a;Remond et al, 2010b) presented the 2D and 3D simulation results obtained during mathematical modeling of wood drying.…”
Section: Introductionmentioning
confidence: 99%